Scientific Mapping of Elderly Food Studies: A Bibliometric Approach - Nafisah Eka Puteri; Muhammad Irfan Febriansyah (Journal of Nutrition Science, 2024)
As the global population ages, there is a growing emphasis on addressing the dietary needs and overall well-being of older individuals. Bibliometric analysis of existing literature on food innovation for the elderly helps identify research trends and gaps, guiding future exploration to better meet the nutritional needs and preferences of this population. The aim of this research is to examine the literature on food and nutrition for older adults through bibliometric analysis. Data was gathered on April 19th, 2024, from the Scopus database by using the search term "elder* AND food". Articles were restricted to specific subject areas and then analyzed using VOSviewer and descriptive statistics. A total of 746 articles published between 1951 and 2024 were discovered, with a notable rise in publications in the past decade. The United States ranked first in the number of published articles, followed by South Korea and Brazil. Keywords were grouped into 11 clusters, encompassing themes such as diet quality, food security, nutritional status, and elderly care. The analysis underscored the global importance of research on elderly nutrition, underscoring the necessity for international cooperation. Recent developments revealed a concentration on food-based dietary guidelines and the management of food bolus for older individuals. The study also addressed limitations, such as potential biases arising from relying on Scopus and excluding non-English publications.